1992
DOI: 10.1128/jvi.66.5.2928-2933.1992
|View full text |Cite
|
Sign up to set email alerts
|

Target epitope in the Tax protein of human T-cell leukemia virus type I recognized by class I major histocompatibility complex-restricted cytotoxic T cells

Abstract: A transacting regulatory gene product p4O' (Tax) of human T-cell leukemia virus type I (HTLV-I) is one of the main target antigens recognized by cytotoxic T lymphocytes (CTL) specific for HTLV-I. A CTL epitope within the Tax protein was identified in this report. HTLV-I-specific CD8+ CTL lines established from two HTLV-I carriers with HTLV-I-associated myelopathy or Sjogren syndrome were previously demonstrated to kill predominantly the target cells expressing HTLV-I Tax. The CTL from two patients showed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(46 citation statements)
references
References 31 publications
2
38
0
4
Order By: Relevance
“…Consistent with the previous data, 5 RMA-H74L cells were lysed by influenza A matrix peptide (FMP 58-66 )-specific CTLs at much lower peptide concentrations than RMA-HHD cells (Figure 1c). Similar results were obtained with different HLA-A*02:01-restricted peptides derived from human papillomavirus (HPV)-E6 (HPV-E6 [29][30][31][32][33][34][35][36][37][38] ), human T-lymphotropic virus (HTLV)-tax (HTLV-tax [11][12][13][14][15][16][17][18][19] ) and human immunodeficiency virus (HIV)-pol (HIV-pol 476-484 ) (Figure 1c), indicating that this phenomenon was not peptide-specific as described in the previous studies. 18 The peptide-binding studies were conducted using the transporter associated antigen processing-2 (TAP-2) deficient cell line, RMA-S 19 expressing HHD (RMA-S-HHD) or HHD-H74L (RMA-S-H74L).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Consistent with the previous data, 5 RMA-H74L cells were lysed by influenza A matrix peptide (FMP 58-66 )-specific CTLs at much lower peptide concentrations than RMA-HHD cells (Figure 1c). Similar results were obtained with different HLA-A*02:01-restricted peptides derived from human papillomavirus (HPV)-E6 (HPV-E6 [29][30][31][32][33][34][35][36][37][38] ), human T-lymphotropic virus (HTLV)-tax (HTLV-tax [11][12][13][14][15][16][17][18][19] ) and human immunodeficiency virus (HIV)-pol (HIV-pol 476-484 ) (Figure 1c), indicating that this phenomenon was not peptide-specific as described in the previous studies. 18 The peptide-binding studies were conducted using the transporter associated antigen processing-2 (TAP-2) deficient cell line, RMA-S 19 expressing HHD (RMA-S-HHD) or HHD-H74L (RMA-S-H74L).…”
Section: Resultssupporting
confidence: 67%
“…HLA-A*02:01-restricted epitopes used were as follows: FMP 58-66 (sequence: GILGFVFTL), 31 HPV-E6 [29][30][31][32][33][34][35][36][37][38] (sequence: TIHDIILECV), 32 HTLV-tax [11][12][13][14][15][16][17][18][19] (sequence: LLFGYPVYV), 33 and HIV-pol 476-484 (sequence: ILKEPVHGV). 34 Synthetic peptides corresponding to the above epitopes were synthesized by Operon Biotechnologies (Tokyo, Japan).…”
Section: Synthetic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with HAM/TSP, a high frequency of HLA-A2-restricted, Taxspecific CTLs correlates positively with virus burden and Tax expression, indicating the existence of continuous antigen presentation [18,19,21,41]. Therefore, the main focus of this study was to determine the maximal route of Tax-specific CTL activation targeting epitope 11-19, as the affinity of this epitope for HLA-A2 was shown to be unusually high [24], and the Tax 11-19specific response is immunodominant frequently in patients with HAM/TSP [16,[25][26][27]. Using in vitro and in vivo priming assays, we demonstrated that DCs could drive an efficient Tax-specific CTL response in naïve PBLs from the normal donor as well as in HHD II mice.…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxic T lymphocytes (CTL) specific for HTLV-I were induccd from peripheral-blood mononuclear cells (PBMC) of a HAM patient by repeated in vitro stimulation with autologous HTLV-I-infected T cells, as described (Kannagi et al, 1991). These CTL predominantly recognize HTLV-I tax, and the main CTL epitope in the tax molecule is a nonapeptide LLFGYPVYV at positions 11 through 19, which is presented with HLA-A2 molecule (Kannagi et al, 1992). These CTL were maintained in a medium containing TL-2 (Shionogi, Osaka, Japan), with periodic in vitro stimulation with HTLV-Iinfected cells.…”
Section: Ctl Arid Atl Cellsmentioning
confidence: 99%